Evaluation of Character Education Strengthening Program at SMA Negeri 2 Kediri - Tsani, Iskandar; Hidayah, Noer; Miftah, Nifa (Didaktika Religia, 2019)
This article aims to review the evaluation of the character strengthening Program (PPK) with models of CIPP models (Context, Input, Process, and Product). The character education reinforcement Program aims to instil the values of the nation’s character formation massively and effectively through the implementation of the key values of the national movement of the Mental revolution. The purpose of this research is to evaluate the implementation of character education strengthening at SMA Negeri 2 Kediri. This article is a result of field research using the Mixed Methods approach. Data sources obtained from principals, deputy principals, educators, and learners. The population is focused on the XI class students with a sample of 38 students while product component data is collected through questionnaires. The results showed that on the Context component, the school’s understanding of PPK was not maximized, environmental support was excellent, and the purpose of the program was obvious. The Input component indicates that the availability of human resources educators and funding sources insufficient categories. The Process component is good enough with evidence of the implementation of class-based programs. Product component Achievement Five main values of PPK students of class XI SMA Negeri 2 Kediri with the average value of a poll obtained by 78.6 shows the very good category in achieving five main values of PPK characters.